2021
DOI: 10.1111/mice.12740
|View full text |Cite
|
Sign up to set email alerts
|

Contract bundling considerations in urban road project scheduling

Abstract: Road project scheduling and contract bundling are two separate concepts that profoundly influence project delivery consequences to key stakeholders. Therefore, agencies espouse initiatives for contract bundling (to reduce project costs) and project scheduling (to reduce user delay costs). Bundling combined with scheduling could potentially yield benefits to both the agency and urban road users. This paper investigates the overall benefits (to the two stakeholders) of optimal schedules with bundling considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Among them, GA, which was introduced into engineering in the 1990s by Adeli and Cheng (1993, 1994a, 1994b, is most widely used. The most widely used multi-objective optimization algorithms are based on GAs (Adeli & Kumar, 1995;Hegazy, 1999;Kim & Adeli, 2001) and PSO (Gutierrez & Kennedy & Eberhart, 1995), with representatives being Non-dominated Sorting Genetic Algorithm II (NSGA-II) (Kociecki & Adeli, 2014;Miralinaghi et al, 2021;Zawidzki & Jankowski, 2019) and multi-objective PSO (MOPSO), respectively. Studies in the field of scheduling (Nemati-Lafmejani et al, 2019) have shown that the solution quality and efficiency of PSO are better than those of GAs.…”
Section: Related Algorithmsmentioning
confidence: 99%
“…Among them, GA, which was introduced into engineering in the 1990s by Adeli and Cheng (1993, 1994a, 1994b, is most widely used. The most widely used multi-objective optimization algorithms are based on GAs (Adeli & Kumar, 1995;Hegazy, 1999;Kim & Adeli, 2001) and PSO (Gutierrez & Kennedy & Eberhart, 1995), with representatives being Non-dominated Sorting Genetic Algorithm II (NSGA-II) (Kociecki & Adeli, 2014;Miralinaghi et al, 2021;Zawidzki & Jankowski, 2019) and multi-objective PSO (MOPSO), respectively. Studies in the field of scheduling (Nemati-Lafmejani et al, 2019) have shown that the solution quality and efficiency of PSO are better than those of GAs.…”
Section: Related Algorithmsmentioning
confidence: 99%
“…The first category addresses the scheduling of projects with durations of several days or even months (Bagloee et al, 2018;Gong & Fan, 2016;Lee, 2009;Lethanh et al, 2017;Li & Fan, 2021;Miralinaghi et al, 2020Miralinaghi et al, , 2021D. Yang et al, 2018;Zheng et al, 2012Zheng et al, , 2014.…”
Section: The Road Scheduling Problemmentioning
confidence: 99%
“…D. Yang et al (2018) considered the nonequilibrium state of traffic and its development during the construction period to an equilibrium state. Miralinaghi et al (2020Miralinaghi et al ( , 2021 developed different frameworks for scheduling long-term road projects in terms of a few months. In this context, static network modeling is used to capture the route choice of travelers.…”
Section: The Road Scheduling Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Bundling projects in the same corridor can lead to lower project costs than when bundling projects at different locations ( 5 ). The bundling of projects that are in different locations also has an adverse effect on the travel time, resulting in public inconvenience ( 7 ). STAs can benefit from the project bundling method if the appropriate bundle size is selected that is feasible to attract a larger number of bidders, increasing the competition in the market and reducing the project cost significantly ( 8, 9 ).…”
mentioning
confidence: 99%